2015
DOI: 10.1016/j.jand.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Physiological and Neurobehavioral Effects of Ramadan Fasting in Preteen and Teenage Boys

Abstract: Ramadan fasting was associated with significant changes in body composition, dietary intake, and sleep patterns. Reductions in attention and iron indices were observed in preteens only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Appropriate sleep durations recommended by the National Sleep Foundation (NSF) for adolescents and adults are approximately 8–10 hours10 with no specific recommendations for athletic populations. However, in the Middle East in particular, individuals obtain insufficient sleep relative to these recommendations across adults (6.2±1.7 hours)11 and adolescents (7 hours),12 13 including adolescent academy soccer players (6.3– 7.3 hours) 14…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate sleep durations recommended by the National Sleep Foundation (NSF) for adolescents and adults are approximately 8–10 hours10 with no specific recommendations for athletic populations. However, in the Middle East in particular, individuals obtain insufficient sleep relative to these recommendations across adults (6.2±1.7 hours)11 and adolescents (7 hours),12 13 including adolescent academy soccer players (6.3– 7.3 hours) 14…”
Section: Introductionmentioning
confidence: 99%
“…During Ramadan, the total amount of sleep may be affected due to late night prayers and major shift in the timing of meals. This would increase the frequency of sleep during the day to compensate (Kadri et al 2000;South et al 2013;Farooq et al 2015). The difficulty in sleeping was almost hardly applicable in this study as the data shows significant declined and remained stable.…”
Section: Discussionmentioning
confidence: 80%
“…This can be attributed to the fact that eating exclusively at nighttime imposes significant alterations on individuals' life style and sleep-wake cycles. The studies described that combination of changes in sleep-wake cycle, food and fluid intakes, and circadian rhythms was likely to affect mental, physical, and [21] social performances .Several subjective or objective assessments on the sleep patterns during Ramadan fasting reported sleep architecture alterations, delayed bedtime, [22,23] and a significant reduction in nocturnal sleep .Their findings showed that sleep loss might be responsible for excessive fatigue and reduced alertness in the daytime. Ramadan fasting also imposes deep impacts on the natural circadian rhythm through significant shifts in sleep [21] patterns, body clock, and other physiological indices .Irritability could be increased during Ramadan fasting which was attributed to reduction in sleep time or nicotine [24] withdrawal .…”
Section: Discussionmentioning
confidence: 99%